1998
DOI: 10.1056/nejm199804093381502
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Alleles of the Collagen Type Iα1 Gene to Bone Density and the Risk of Osteoporotic Fractures in Postmenopausal Women

Abstract: The COLIA1 polymorphism is associated with reduced bone density and predisposes women to osteoporotic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
247
3
16

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(294 citation statements)
references
References 33 publications
28
247
3
16
Order By: Relevance
“…However, the r 2 for the linkage disequilibrium was relatively small, and the two SNPs were not within the same LD block (Supplementary Figure). Thus, the possibility cannot be excluded that the intronic SNP may affect the expression level of the gene via an unknown mechanism, similar, for example, to the actions of intronic SNPs in Calpain10 [28] and COLIA1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the r 2 for the linkage disequilibrium was relatively small, and the two SNPs were not within the same LD block (Supplementary Figure). Thus, the possibility cannot be excluded that the intronic SNP may affect the expression level of the gene via an unknown mechanism, similar, for example, to the actions of intronic SNPs in Calpain10 [28] and COLIA1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on a polymorphism within intron 1, which is situated at a binding site for the transcription factor Sp1. The COLIA1 Sp1-binding site polymorphism has been associated with various osteoporosis-related phenotypes, including bone density (Grant et al 1996;Uitterlinden et al 1998), fragility fractures (Grant et al 1996;Uitterlinden et al 1998), postmenopausal bone loss (Harris et al 2000;MacDonald et al 2001), bone geometry (Qureshi et al 2001), bone quality (Mann et al 2001), and bone mineralization . Functional analysis has shown that the osteoporosis-associated T allele ("s") of the Sp1 polymorphism is associated with increased DNA-protein binding, increased transcription, and abnormally increased production of the COLIA1 mRNA and protein (Mann et al 2001).…”
Section: Collagen Type I␣ Imentioning
confidence: 99%
“…Because sequence variations in COL1A1 , COL1A2 , LRP5 , OPG , and ESR1 increase the risk of low bone mass or osteoporotic fractures, we first examined their possible role in the pathogenesis of stress fractures by scanning all their exons and exon boundaries in the 72 subjects and the 120 controls for mutations using CSGE [14,15,17,20]. The analysis revealed no putative disease-causing mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations or allelic variants in the genes leading to a variety of bone pathologies that increase bone fragility, such as collagen I, ( COL1A1 and COL1A2 ) [14,15], vitamin D receptor ( VDR ) [16], osteoprotegerin ( OPG ) [17], calcitonin receptor ( CTR ) [18], estrogen receptor ( ESR ) [19], low density lipoprotein receptor-related protein 5 ( LRP5 ) [20], and interleukin 6 ( IL-6 ) [21] may also increase the risk of stress fractures. Sequence variations in these genes are associated with a low peak bone mass, osteoporosis, osteogenesis imperfecta, osteoporosis-pseudoglioma syndrome, and high bone mass, but their role in predisposing to stress fracture is not clear [14-21].…”
Section: Introductionmentioning
confidence: 99%